2017
DOI: 10.1177/1534734616685636
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Anemia and Comorbid Leg Ulcer Treated With Curative Peripheral Blood Stem Cell Transplantation

Abstract: Allogeneic bone marrow transplantation or peripheral blood stem cell transplantation (PBSCT) are the only curative therapies for patients with sickle cell disease (SCD). Once the patients have successfully undergone transplantation and engrafted, the hallmark of hemolytic anemia resolves, and normal hemoglobin levels are achieved. Some transplant protocols exclude patients with open wounds, including leg ulcers, because of infection risks associated with transplantation and long-term immunosuppression required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…72 A 30-year-old woman with SCD and leg ulcers treated with allogeneic keratinocytes had complete ulcer recovery in 3 months, with no recurrence during the 8-month follow-up period. 73 Connor et al 74 observed that a 37-year-old man with a SCD-related ulcer recovered completely after 16 months with treatment of hematopoietic stem cell allograft.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…72 A 30-year-old woman with SCD and leg ulcers treated with allogeneic keratinocytes had complete ulcer recovery in 3 months, with no recurrence during the 8-month follow-up period. 73 Connor et al 74 observed that a 37-year-old man with a SCD-related ulcer recovered completely after 16 months with treatment of hematopoietic stem cell allograft.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Vasodilation is reduced in patients with SCD and may have other consequences, such as the appearance of leg ulcers [94,106,107]. These lower limb ulcer lesions represent 8 to 10% of the cases and have a higher incidence in people with SCA males and in the age group between 10 and 50 years [99,107,108,109].…”
Section: Clinical Consequences Of the Presence Of Hb Smentioning
confidence: 99%
“…Ulcerations may appear after trauma, insect bites, excessive dryness of the skin or spontaneously generally in the ankle or malleolar region (middle or lateral portion), where there are less subcutaneous tissue and blood flow as a consequence of tissue hypoxia, endothelial dysfunction, and vaso-occlusion [107,108,110]. Infections in these patients are also a major cause of concern both in childhood and in adulthood [76,78,111,112].…”
Section: Clinical Consequences Of the Presence Of Hb Smentioning
confidence: 99%
“…The treatment of chronic painful wounds of sickle cell disease (SCD) is a significant challenge, and stem cell therapy may also be an alternative (Meneses et al, 2016;Connor et al, 2017). Although allogeneic bone marrow transplantation or peripheral blood stem cell transplantation are considered the only curative therapies for patients with SCD (Connor et al, 2017), the pain symptom seems not to be solved for these patients. Darbari et al (2019) recently published some impressive results on pain relief and reduction of the need for opioids in a cohort study in patients with SCD undergoing haematopoietic stem cell transplant (HSCT).…”
mentioning
confidence: 99%
“…The treatment of chronic painful wounds of sickle cell disease (SCD) is a significant challenge, and stem cell therapy may also be an alternative (Meneses et al, 2016;Connor et al, 2017). Although allogeneic bone marrow transplantation or peripheral blood stem cell transplantation are considered the only curative therapies for patients with SCD (Connor et al, 2017), the pain symptom seems not to be solved for these patients.…”
mentioning
confidence: 99%